PENGARUH PENGGUNAAN GAME ONLINE TERHADAP PERILAKU SOSIAL SISWA KELAS V SDN 6 LALAN KEC. LUBUK TAROK KAB. SIJUNJUNG - Martha, Alfroki; Zelia, Jozi (LP2M Universitas Adzkia, 2024)
This research was motivated by the widespread use of online games among various age groups, from children to adults. The engaging features and strategies in these games have led some students to secretly bring their phones to school to continue unfinished gameplay. This study uses a descriptive quantitative method to describe the research object based on collected data. Data collection techniques included questionnaires, observation, interviews, and documentation. The data were analyzed using simple linear regression. The hypothesis test results showed that the t-value was greater than the t-table value (4.784 > 1.987), indicating a significant influence of online game usage on social behavior. The significance value of 0.000 < 0.05 further supports this finding. Therefore, it can be concluded that the use of online games has an impact on students’ social behavior.